2002
DOI: 10.1111/j.1365-2621.2002.tb11371.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing and Frozen Storage on Chemical and Microbiological Characteristics in Sheep Milk Cheese

Abstract: Most chemical components and water activity of an the Los Pedroches' brand ewes' milk cheese were not altered by frozen storage. Lactic acid concentration and pH were significantly different (p Ͻ Ͻ Ͻ Ͻ Ͻ 0.05) in control cheeses and those kept in frozen storage for 3 and 6 months from those stored for 9 months. Proteolysis continued slowly during frozen storage, with significantly higher rates of non protein nitrogen and amino acid nitrogen (p Ͻ Ͻ Ͻ Ͻ Ͻ 0.05) present at the end of the storage period. Counts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 17 publications
4
17
0
1
Order By: Relevance
“…However, one of the indicators of the secondary proteolysis, the NPN%, presented significant differences between the NF and the frozen samples, with higher values in the frozen samples (P < 0•05) ( Table 1), meaning that the freezing process did not prevent the secondary proteolysis mechanisms from occurring; they continue to develop, as has been previously reported by other authors which studied the impact of freezing on proteolysis during cheese ripening (Bertola et al 1996;Tejada et al 2002;Verdini et al 2003;Graiver et al 2004;Van-Hekken et al 2005;Verdini et al 2005). Freezing led to higher NPN concentrations, probably due to the damage caused by the ice crystals on (1) casein matrix and (2) the starter cells that liberate proteolytic enzymes to the media (Graiver et al 2004), making them more available for the enzymatic activity.…”
Section: Impact Of Freezing On Chemical Propertiessupporting
confidence: 66%
“…However, one of the indicators of the secondary proteolysis, the NPN%, presented significant differences between the NF and the frozen samples, with higher values in the frozen samples (P < 0•05) ( Table 1), meaning that the freezing process did not prevent the secondary proteolysis mechanisms from occurring; they continue to develop, as has been previously reported by other authors which studied the impact of freezing on proteolysis during cheese ripening (Bertola et al 1996;Tejada et al 2002;Verdini et al 2003;Graiver et al 2004;Van-Hekken et al 2005;Verdini et al 2005). Freezing led to higher NPN concentrations, probably due to the damage caused by the ice crystals on (1) casein matrix and (2) the starter cells that liberate proteolytic enzymes to the media (Graiver et al 2004), making them more available for the enzymatic activity.…”
Section: Impact Of Freezing On Chemical Propertiessupporting
confidence: 66%
“…Alichanidis et al (1981) and Fontecha et al (1996) also found a significant decrease in the number of starter microorganisms during frozen storage of semi-hard sheep milk cheeses. According to Tejada et al (2002) lactobacilli counts in sheep milk cheeses frozen for 9 months were significantly (P < 0.05) lower than those detected in control cheeses and in cheeses frozen for 3 months. There was also a decrease in lactococci counts after 6 months of Portman (1971) found that the size of the lactic acid bacteria population during frozen storage of cheese curd contracted approximately 10 times as compared with its initial amount contained in the fresh curd.…”
Section: Discussionmentioning
confidence: 68%
“…thermophilus. Other authors (Alichanidis et al 1981;Tejada et al 2002) also established a greater decrease in the number of lactobacilli during frozen storage of sheep milk cheeses as compared to the other lactic acid microorganisms.…”
Section: Discussionmentioning
confidence: 88%
“…Declines of almost 2 log units were recorded for fresh ovine milk cheese made with a L. lactis starter stored at À20 C for 4 months after thawing (Fontecha et al, 1994). However, Tejada et al (2002) recorded no decrease in counts of lactococci, lactobacilli, leuconostocs, enterococci, staphylococci and micrococci in fully ripened raw ovine milk cheese frozen for 3 or 6 months, and decreases of more than 1 log unit for counts of enterobacteriaceae, coliforms, moulds and yeasts.…”
Section: Lactic Acid Bacteria and Aminopeptidase Activity In Curdsmentioning
confidence: 87%